Ludell, Rawlins County - Solko, Greg (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study of Ludell, Kansas and the lack of name continuity in Rawlins County includes a map analysis, a printed memoir-history by a resident, photographs of the town site, and an author’s firsthand accounts of interviews conducted with those who lived in the community.
Greg Solko, “Ludell, Rawlins County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/130.
Keywords: Atwood; Ludell Township; Prague; Rawlins County; Sappa Creek; Civilian Conservation Corps